Monday

October 20, 2014

October 20, 2014

Posted by **What's the Difference?** on Thursday, April 26, 2012 at 3:29pm.

y = (2x^2+3)(x-1)

at x=2.

a = 11

b = 08

c = 19

d = 16

- Calculus -
**Reiny**, Thursday, April 26, 2012 at 3:40pmI would expand it, then take the derivative

then subbing in x=2 can be done mentally

- Calculus -
**I Need Help**, Thursday, April 26, 2012 at 4:18pmI did that and got 19. Is this right?

**Answer this Question**

**Related Questions**

College Calculus - Let f(x) = 3x^2 - 2x + 1 a) write an equation of the line ...

Calculus - Find the slope and the equation of the tangent line to the graph of ...

Calculus - 55. Find an equation of the tangent line to the graph of f(x) =x^3 - ...

calculus - find the equation of a quadratic function whose graph is tangent at x...

Calculus - Find the slope m of the tangent line to the graph of the function at ...

Calculus - Find the slope m of the tangent line to the graph of the function at ...

Calculus PLEASE HELP - Find the slope m of the tangent line to the graph of the ...

Calculus - Find the slope m of the tangent line to the graph of the function at ...

Calculus - Let f(x)=3x^4-2x^2+3 a) find f'(x) Answer: f'(x)=12x^3-4x b) find the...

cal - find the equation of a quadratic function whose graph is tangent at x=1 to...